Efficient Modeling of NMR Parameters in Carbon Nanosystems - Kupka, Teobald; Stachów, Michał; Chełmecka, Elżbieta; Pasterny, Karol; Stobińska, Magdalena; Stobiński, Leszek; Kaminský, Jakub (Journal of chemical theory and computation, 2013)
Rapid growth of nanoscience and nanotechnology requires new and more powerful modeling tools. Efficient theoretical modeling of large molecular systems at the ab initio and Density Functional Theory (DFT) levels of theory depends critically on the size and completeness of the basis set used. The recently designed variants of STO-3G basis set (STO-3Gel, STO-3Gmag), modified to correctly predict electronic and magnetic properties were tested on simple models of pristine and functionalized carbon nanotube (CNT) systems and fullerenes using the B3LYP and VSXC density functionals. Predicted geometries, vibrational properties, and HOMO/LUMO gaps of the model systems, calculated with typical 6-31G* and modified STO-3G basis sets, were comparable. The (13)C nuclear isotropic shieldings, calculated with STO-3Gmag and Jensen's polarization consistent pcS-2 basis sets, were also identical. The STO-3Gmag basis sets, being half the size of the latter one, are promising alternative for studying (13)C nuclear magnetic shieldings in larger size CNTs and fullerenes.